Evaluation of the performance of joint forest management (JFM) programme : case of Dambwa Forest Reserve in Livingstone District, Zambia - Phiri, Maxwell (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScFor (Forest and Wood Science))--University of Stellenbosch, 2009.